Correlations between ATF3 polymorphisms and ischemic stroke in Dali, Yunnan Province, as determined by a case-control study - Yang, Yunhui; Wang, Pengyu; Wang, Min; Wang, Guangming (BMC neurology, 2025)
Genetic factors play an important role in ischemic stroke (IS) onset. Activating transcription factor 3 (ATF3) is a known IS biomarker; however, the association between ATF3 polymorphisms and susceptibility to IS remains unclear. Therefore, we aimed to explore the association between ATF3 single-nucleotide polymorphisms (SNPs) and genetic susceptibility to IS in a population in Dali, Yunnan, China. We included 145 patients with IS and 127 healthy controls in this case-control study. ATF3 SNP sites (rs1105899, rs1008737, rs1195474, and rs1195472) were genotyped using SNaPshot detection. Venous serum glucose (VSG), white blood cell count, total cholesterol, triglycerides, low-density lipoprotein cholesterol, and systolic blood pressure (SBP) were IS risk factors; VSG had the highest impact on IS susceptibility, whereas SBP had the lowest. Genotype distributions of rs1105899, rs1008737, and rs1195472 polymorphisms in the control group conformed to the Hardy-Weinberg equilibrium. Association analysis between ATF3 polymorphisms and IS risk showed that rs1105899, rs1008737, and rs1195474 ATF3 polymorphisms were not significantly associated with IS risk. In the codominant and superdominant model of the rs1195472 [C/T] loci, CT genotype can reduce the risk of stroke, compared with TT and CC genotypes. Haplotype AGAC was an inhibitory factor for IS. The GTEx database showed that the rs1195472 CT genotype increased ATF3 expression and was associated with its expression in individual tissues. The rs1195472 polymorphism was associated with IS risk in our study population; no significant correlation was noted between rs1105899, rs1008737, and rs1195474 polymorphisms and IS.